The Role of Bissu and Their Existence in Modern Bugis Society of South Sulawesi - Rahmat, Laodemuh; Hartono; Purnomo, Sucipto Hadi (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2025)
In the period before the influence of Islam entered the Bugis Bone kingdom, the Bugis Kingdom was always known for its mabissu tradition. The word bissu itself comes from the word